3D printed unmanned ground vehicle - Gan, Bee Li (2016)
This project aims to design an aesthetically pleasing but simple 3D printed unmanned ground vehicle (UGV) with the combined goal to create an online educational platform. The 3D printed UGV is created using computer aided drafting and designing (CAD) software such as Solidworks and Autodesk Inventor Professional before being converted into an STL (STereoLithography) file for 3D printing. The design of the UGV focuses on utilizing a handful of printed components which can be used to create multiple vehicle designs, be it elongated, wide and so on. The cover or shell of the vehicle is also attempted using multiple CAD techniques and compared in terms of ease of usage. This report also covers multiple wireless communication types through Bluetooth, XBee modules and Arduino YUN wireless transmission respectively to provide multiple options to the online platform. As the project intention is enable pre-engineering students to recreateit, an online platform is built- Embark360.weebly.com, to provide procedures in manageable portions to the readers. This also leads the project to focus greatly on simplicity and ease of usage.